Properties of Medium Density Fibreboard from Oil Palm (Elaeis Guineensis, Jacq.) Fibres - Liew, Lionel Li Lung (1996)

(untitled)
This study aimed to determine the possibility of processing the oil palm trunk, frond and empty fruit bunch (EFB) fibres for medium density fibreboard (MDF) production. Vascular bundles from the three major fibrous components of oil palm tree was collected after they were disintegrated by an 'All Palm Fractionator' machine. A study on the vascular bundles recovery on the three parts of oil palm tree revealed that EFB has the highest vascular bundles recovery rate (90.49%) followed by frond (75.28%) and trunk (48.65%). However, vascular bundle from the trunk has the most favourable colour (light creamy) for MDF manuf acturing. The fibre morphology study indicated that the morphological properties of all the three types of fibres were adequate to produce good strength fibre composite eventhough their fibre length, coefficient of suppleness and Runkle ratio might not be as good as softwood fibre.